Drosophila melanogaster prat, a purine de novo synthesis gene, has a pleiotropic maternal-effect phenotype. - Malmanche, N.; Clark, D.V. (Genetics, 2004)
In Drosophila melanogaster, two genes, Prat and Prat2, encode the enzyme, amidophosphoribosyltransferase, that performs the first and limiting step in purine de novo synthesis. Only Prat mRNA is present in the female germline and 0- to 2-hr embryos prior to the onset of zygotic transcription. We studied the maternal-effect phenotype caused by Prat loss-of-function mutations, allowing us to examine the effects of decreased purine de novo synthesis during oogenesis and the early stages of embryonic development. In addition to the purine syndrome previously characterized, we found that Prat mutant adult females have a significantly shorter life span and are conditionally semisterile. The semisterility is associated with a pleiotropic phenotype, including egg chamber defects and later effects on embryonic and larval viability. Embryos show mitotic synchrony and/or nuclear content defects at the syncytial blastoderm stages and segmentation defects at later stages. The semisterility is partially rescued by providing Prat mutant females with an RNA-enriched diet as a source of purines. Our results suggest that purine de novo synthesis is a limiting factor during the processes of cellular or nuclear proliferation that take place during egg chamber and embryonic development.